Interactive Effects of Sulfide Addition and Heat Pretreatment on Hydrogen Production via Dark Fermentation - Tae-Hoon Kim; Yun-Ju Jeon; Sungjin Park; Ji-Hye Ahn; Junsu Park; Yeo-Myeong Yun (Fermentation, 2025)
Despite being recognized as toxic in anaerobic systems, sulfide’s potential to enhance hydrogen fermentation via microbial modulation remains underexplored. This study evaluated the combined effects of sulfide concentration (0–800 mg S/L) and heat pretreatment on hydrogen production during dark fermentation (DF). Without pretreatment, hydrogen yield reached 83 ± 2 mL/g COD at 0 mg S/L but declined with increasing sulfide, becoming negligible at 800 mg S/L. In contrast, heat-pretreated inocula showed markedly improved performance: peak cumulative production (4628 ± 17 mL) and yield (231 ± 1 mL/g COD) were attained at 200 mg S/L, while the maximum production rate (1462 ± 64 mL/h) occurred at 400 mg S/L. These enhancements coincided with elevated acetic and butyric acids, indicating a metabolic shift toward hydrogen-producing pathways. The microbial analysis of heat-pretreated samples revealed an enrichment of Clostridium butyricum (from 73.1% to 87.5%) and Clostridium perfringens, which peaked at 13.5% at 400 mg S/L. This species contributed to butyric acid synthesis. At 800 mg S/L, Clostridium perfringens declined sharply to 0.6%, while non-hydrogenogenic Levilinea saccharolytica proliferated, correlating with reduced butyric acid and hydrogen output. These findings indicate that sulfide supplementation, when combined with heat pretreatment, selectively restructures microbial communities and metabolic pathways, enhancing DF performance.